Ambrose Houle interview - Houle, Ambrose; Beaver, Alfred J. (Canadian Plains Research Centre, 1980)
8 p. transcript of an interview with Ambrose Houle, conducted by Alfred J. Beaver on an unknown date, possibly in 1980. Tape number IH-286, transcript disc 33. Mr. Ambrose Houle, aged 61, a non-treaty person, tells his story of loss of treaty status, and promises of reserve at Trout Lake. Other no